Modification and validation of the test procedure for determination of sub-visible particulate matter in parenteral solutions, using the Coulter method - A. A. Voropaev; O. V. Fadeikina; D. S. Davydov; A. A. Movsesyants (Биопрепараты: Профилактика, диагностика, лечение)
The State Pharmacopoeia of the Russian Federation, 14th edition provides for determination of sub-visible particles (less than 100 µm in size) in parenteral dosage forms using the Coulter method, in addition to the light obscuration particle count test and microscopy. However, the proposed 100 µm aperture tube does not enable assessment of the whole range of sub-visible particle sizes. Therefore, research is needed to find optimal test conditions for determination of sub-visible particulate matter by the Coulter method. The aim of the study: modification of the Coulter-based procedure using a 200 µm aperture tube, and performance of validation studies. Materials and methods: Multisizer 4e Coulter counter, suspensions of reference latex particles (10 µm, 20 µm, and 43 µm), and a particulate count reference standard containing 0.998 × 106 particles/mL were used in the study. The following parameters were assessed during validation: accuracy, repeatability, linearity. Results: the study confirmed the feasibility of using the modified Coulter-based procedure with a 200 µm aperture tube. The following values were obtained during validation of the modified test procedure: accuracy was 5.3% (deviation from the mean value) as compared to the particulate count reference standard, and 4.2% as compared to the light obscuration method. Repeatability was 1% (relative standard deviation) for the particle concentration of approximately 10000 per 1 mL, and 7.6% for the particle concentration of approximately 300 per 1 mL. The study demonstrated the linearity of the procedure, the linear correlation coefficient was more than 0.99. Conclusions: the studied validation parameters of the modified test procedure were shown to comply with the acceptance criteria. The modified test procedure will enable assessment of the whole range of sub-visible particle sizes when testing parenteral solutions for particulate contamination: sub-visible particles.